2022
DOI: 10.3390/atmos13020172
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality outside Schools in Newcastle upon Tyne, UK: An Investigation into NO2 and PM Concentrations and PM Respiratory Deposition

Abstract: Air pollution is the principal environmental threat to public health in the UK. Ever-increasing evidence links ambient air pollutants, preventable diseases, and health inequalities. Children are particularly vulnerable to harmful effects due to their short height, developing lungs, and higher rate of respiration. Using data from air quality monitors around schools, we investigated 2018–2019 ambient NO2, PM10, PM2.5, and PM1 concentrations at 12 schools in Newcastle upon Tyne, UK. We compared findings with EU/U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Particle deposition and inhalation rate through respiratory tracts are estimated using algebraic and semi-empirical deposition models (Hofmann, 2011). We adopted a deposition fraction (DF) model (ICRP, 1994) of the International Commission on Radiological Protection (ICRP) since it is a commonly used approach by researchers (Keast et al, 2022;Martins et al, 2015b) and in our previously published work (e.g. Abhijith and Kumar, 2021;Kumar et al, 2018;Kumar and Goel, 2016).…”
Section: Exposure Dosesmentioning
confidence: 99%
“…Particle deposition and inhalation rate through respiratory tracts are estimated using algebraic and semi-empirical deposition models (Hofmann, 2011). We adopted a deposition fraction (DF) model (ICRP, 1994) of the International Commission on Radiological Protection (ICRP) since it is a commonly used approach by researchers (Keast et al, 2022;Martins et al, 2015b) and in our previously published work (e.g. Abhijith and Kumar, 2021;Kumar et al, 2018;Kumar and Goel, 2016).…”
Section: Exposure Dosesmentioning
confidence: 99%
“…These data show that census tracts with higher proportions of people who identify as Hispanic or Latino and American Indian and Alaska Native tend to have worse air quality. This is not a new finding; many other studies have found an air quality discrepancy with respect to race and ethnicity. ,,,,,, Population-weighted averages, while easy to calculate, sometimes mask important distributional insights in the data Table presents the Spearman correlation between NO 2 column and surface PM 2.5 concentration with racial or ethnic group population fraction in census tracts in Denver.…”
Section: Results and Discussionmentioning
confidence: 85%
“…Respiration deposition dosage (RDD) is estimated by using the International commission on radiological protection (ICRP) 1994 model (He and Gao, 2021;Keast et al, 2022;Hinds and Zhu, 2022). We estimated operators' respiratory deposition doses (RDD) of PM (PM1, PM2.…”
Section: Exposure Estimationmentioning
confidence: 99%